Risk of Psychiatric Problems for People with Negative Psychosocial Impacts in Compared to Positive Attitude during Covid-19 Pandemic: A Systematic Review - Yuliana, . (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2021)
Introduction: COVID-19 pandemic has negative or positive psychosocial impacts on society. Fear, uncertainty, insomnia, depression, anxiety, and suicide are the negative psychosocial impacts. These psychosocial impacts may cause psychiatric problems. This paper aims to describe the risk of psychiatric problems for people with negative psychosocial impacts in comparison to positive attitudes during the COVID-19 pandemic.Methods: This systematic literature review used these keywords: ‘fear’, ‘uncertainty’, ‘COVID-19’, ‘psychiatric problem’ , and ‘society’. The search engines used were PubMed and Science Direct. There were 302 papers from PubMed and 134 papers from Science Direct at the beginning. To ascertain the quality of the selection, the process was done twice. Narrative reviews were excluded. Finally, 19 manuscripts were selected for review. PRISMA guidelines were used in the reviewing procedures.Results: From 18 cross-sectional studies and one randomized control trial, it was found that females and the elderly are prone to anxiety and depression. Other risk factors are low income, signs of infection, previous contact history with COVID-19 patients, too much information about COVID-19, and pseudoscientific beliefs. Positive protective factors are good self-talk skills, coping strategy mechanisms, compliance with the rules, and a high level of mental resilience.Conclusion: Anxiety and depression prevention related to Covid-19 can be done through strengthening the positive protective factor and minimize the risk factors. COVID-19 pandemic should be seen as an opportunity to strengthen positive mental attitudes.